Fulminant Perianal Donovanosis Manifesting as Septic Shock in a Treatment-Naïve AIDS Patient: A Clinico-Pathological Case Report - Rahmat Firdaus Dwi Utama; Muhammad Eko Irawanto; Ayu Kusuma Dewi; Shelly Lavenia Sambodo; Stella Gracia Octarica; Sugih Primas Adjie (Open Access Indonesian Journal of Medical Reviews, 2025)
Donovanosis (Granuloma Inguinale), caused by Klebsiella granulomatis, is a rare sexually transmitted infection that can follow a devastating course in severely immunocompromised individuals. Its clinical progression in the context of advanced acquired immunodeficiency syndrome (AIDS) is not extensively documented. We present a case of fulminant donovanosis to illustrate its potential for rapid systemic deterioration and mortality. A 20-year-old Indonesian man, with a recent diagnosis of human immunodeficiency virus (HIV) for which he was treatment-naïve, presented with a two-month history of extensive, painful perianal ulcerations. Clinical examination revealed large, coalescing, "beefy-red" ulcers in the perianal and gluteal regions. Laboratory investigations confirmed profound immunosuppression (CD4+ T-cell count: 3 cells/µL; HIV viral load: >750,000 copies/mL). The diagnosis of donovanosis was definitively established by the microscopic identification of pathognomonic intracellular Donovan bodies on a Giemsa-stained tissue smear, with findings corroborated by histopathological analysis of a skin biopsy. Despite the initiation of appropriate antibiotic and supportive therapy, the patient's condition rapidly progressed to septic shock and multi-organ dysfunction syndrome, leading to his death within six days of hospital admission. In conclusion, this case highlights the aggressive, life-threatening nature of donovanosis in the setting of advanced AIDS. The profound collapse of cell-mediated immunity likely facilitated uncontrolled bacterial replication and systemic dissemination, rendering standard antibiotic therapy ineffective. This report serves as a critical clinical reminder to maintain a high index of suspicion for donovanosis in immunocompromised patients presenting with atypical anogenital ulcers, as early diagnosis and aggressive multimodal management are paramount.